Parents and nurses balancing parent-infant closeness and separation: a qualitative study of NICU nurses' perceptions - Feeley N; Genest C; Niela-Vilen H; Charbonneau L; Axelin A (BIOMED CENTRAL LTD, 2022)
Background: When a newborn requires neonatal intensive care unit (NICU) hospitalization, parent and infant experience an unusual often prolonged separation. This critical care environment poses challenges to parent-infant closeness. Parents desire physical contact and holding and touching are particularly important. Evidence shows that visitation, holding, talking, and skin to skin contact are associated with better outcomes for infants and parents during hospitalization and beyond. Thus, it would be important to understand closeness in this context. The purpose of this study was to explore from nurses' perspective, what do parents and nurses do to promote parent-infant closeness or provoke separation.Methods: Qualitative methods were utilized to attain an understanding of closeness and separation. Following ethics approval, purposive sampling was used to recruit nurses with varying experience working different shifts in NICUs in two countries. Nurses were loaned a smartphone over one work shift to record their thoughts and perceptions of events that occurred or experiences they had that they considered to be closeness or separation between parents and their hospitalized infant. Sample size was determined by saturation (18 Canada, 19 Finland). Audio recordings were subjected to inductive thematic analysis. Team meetings were held to discuss emerging codes, refine categories, and confirm these reflected data from both sites. One overarching theme was elaborated.Results: Balancing closeness and separation was the major theme. Both parents and nurses engaged in actions to optimize closeness. They sought closeness by acting autonomously in infant caregiving, assuming decision-making for their infant, seeking information or skills, and establishing a connection in the face of separation. Parents balanced their desire for closeness with other competing demands, such as their own needs. Nurses balanced infant care needs and ability to handle stimulation with the need for closeness with parents. Nurses undertook varied actions to facilitate closeness. Parent, infant and NICU-related factors influenced closeness. Consequences, both positive and negative, arose for parents, infants, and nurses.Conclusion: Findings point to actions that nurses undertake to promote closeness and help parents cope with separation including: promoting parent decision-making, organizing care to facilitate closeness, and supporting parent caregiving.